L’apport de l’assurance au financement de l’économie française - Bertaux, Robert (Assurances, 1985)
In this article, Mr. Robert Bertaux looks at how French firms use assets in reserve to guarantee their insurance contracts issued by French companies. ln addition to various stocks, shares and real estate investments, private and public insurers take an active interest in small and medium size companies and regional development corporations. In this manner, private or nationalized French life assurance firms fulfill one of their major roles while securing the solvency they need for their portfolio.